SURVEI TINGKAT KEMAMPUAN TEKNIK DASAR DAN KONDISI FISIK PADA SISWA SEKOLAH SEPAK BOLA (SSB) RANTAI BAJA KOTA PURWODADI TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research was to determine the basic engineering and the physical condition of the student School Football ( SSB ) Ratai Steel in 2013 . This study uses the basic techniques of test instruments soccer skills . Descriptive results of calculations known percentage of students overall physical condition of the school football ( SSB ) Steel Chain , it can be concluded that the overall physical condition of the football school students ( SSB ) Steel Chain In 2013 most of the 60 ( 60 % ) of students included in the medium category . To test the level of basic engineering skills football soccer school students ( SSB ) Steel Chain in 2013 note that 74 ( 74 % ) of students included in both categories . The conclusions of this study is the overall physical condition of the football school students ( SSB ) Steel Chain city Purwodadi most 60 students ( 60 % ) included in the medium category , 38 students ( 38 % ) included in both categories , 2 students ( 2 % ) included in the category of less and no students were included in both categories once and less so . To test the basic movement skills soccer soccer school students ( SSB ) Steel Chain Purwodadi town is known that 74 ( 74 % ) of students included in either category , 26 ( 26 % ) of students included in the category of moderate and no students are included in the category of less